Synthetic cannabinoid-associated coagulopathy secondary to long-acting anticoagulant rodenticides: Observational case series and management recommendations. Issue 36 (September 2019) - Bahouth, Mona N.; Kraus, Peggy; Dane, Kathryn; Plazas Montana, Manuela; Tsao, William; Tabaac, Burton; Jasem, Jagar; Schmidlin, Holly; Einstein, Evan; Streiff, Michael B.; Shanbhag, Satish
Abstract : Abstract: Synthetic cannabinoids have become increasingly popular drugs of abuse due to low cost and inability to detect these substances on routine drug screenings. In the United States, incidence of synthetic cannabinoid contamination with long-acting anticoagulant rodenticides (LAARs) resulting in coagulopathy and bleeding complications has been described. We sought to describe the natural history, management approach, and outcomes of bleeding secondary to synthetic cannabinoid-associated LAAR toxicity in an observational case series of patients evaluated at an urban academic medical system. We conducted an observational study of patients with suspected exposure to LAAR-contaminated synthetic cannabinoids and associated bleeding treated within the Johns Hopkins Health System. In this 16 subject cohort, hematuria was the most common bleeding symptom at presentation. The majority of the cohort (75%) had international normalized ratio (INR) > 9.6 at presentation. Of the 13 patients with brodifacoum testing, 12/13 (92%) were positive. Twelve patients (75%) had at least 1 INR value below 2 within 24 hours of the first INR measurement. Of this cohort, 1/16 (6%) died in hospital. The median length of hospital stay was 4 days, (interquartile range = 3–6). The average cost of pharmacological treatment for coagulopathy during inpatient hospitalization was 5300 (range, 2241–8086). In patients presenting with unexplained coagulopathy it is important for emergency department providers to consider LAAR intoxication and consider formal testing for brodifacoum to assist with treatment planning. Use of a standardized management algorithm including intravenous/oral vitamin K, judicious use of blood products and close laboratory monitoring is essential to optimizing outcomes. Abstract : Supplemental Digital Content is available in the text